2013
DOI: 10.1590/s0101-32892013000200014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito imediato da manipulação osteopática tibiotársica no equilíbrio estático de mulheres jovens

Abstract: RESUMO Objetivou-se verificar o efeito imediato da manipulação osteopática para anterioridade tibiotársica sobre o equilíbrio estático, em mulheres jovens. Metodologia: Vinte mulheres foram divididas igualmente em dois grupos: manipulação do tornozelo (GMT) e controle (GC). Analisou-se o deslocamento ântero-posterior (Y) e médio-lateral (X), de olhos abertos e fechados, em um Baropodômetro. Resultados: Na análise intergrupos, o GMT apresentou

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…Two studies were rated on the PEDro scale, consider clinical trials, but in one of them, the sample was intentional (women only), non-randomized, but separated into groups according to the presence or absence of osteopathic dysfunction. (20) Despite this, this study blinded by the evaluator, presented satisfactory inter-groups results evidenced through graphs. Other study, best rated on the scale, it is a randomized single blind clinical trial, in which the sample eligibility criteria are clear and satisfactory, the OM was carried out by only one therapist and results evaluated inter-group.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Two studies were rated on the PEDro scale, consider clinical trials, but in one of them, the sample was intentional (women only), non-randomized, but separated into groups according to the presence or absence of osteopathic dysfunction. (20) Despite this, this study blinded by the evaluator, presented satisfactory inter-groups results evidenced through graphs. Other study, best rated on the scale, it is a randomized single blind clinical trial, in which the sample eligibility criteria are clear and satisfactory, the OM was carried out by only one therapist and results evaluated inter-group.…”
Section: Discussionmentioning
confidence: 78%
“…In studies in which there was handling of the ankle and foot (20,21) the instrument used to balance evaluation was stabilometry, which consist in quantifying anteroposterior and mediolateral oscillation of the body, while the individual remains in a baropodometry platform. (22,23) This technique is commonly used to investigate changes in foot stability after the application of any therapeutic procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This no standardization could make it diffi cult the repeatability of the test in a second time. Some authors instructed participants to keep their feet in a comfortable position [11][12][13][14][15] , others to keep the feet positioned just in parallel 13,[16][17][18] and distanced according to hip width 19 .…”
Section: Feet Positioningmentioning
confidence: 99%
“…Regarding the positioning of the mouth, some evaluators instructed to close the mouth without gripping 17 or have the mouth half open 13 . Some studies have shown a relationship between occlusion with bucal grip in balance, showing better performance in the balance when performed the occlusion with bucal grasp; but there is not enough scientifi c evidence to support this relationship 22 .…”
Section: Mouth Positioningmentioning
confidence: 99%